ELIMINASI PEMBOROSAN PADA PROSES PRODUKSI PIA SUSU BALI MENUNGGUNAKAN PENDEKATAN LEAN MANUFACTURING (STUDI KASUS: CV X) - Putu Kevin Dinata Arsana; Mia Juliana; Made Nindya Kirana (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to identify and reduce waste in the production process of Balinese milk pia at CV X using the Lean Manufacturing approach. The company faces issues such as production capacity constraints in meeting fluctuating demand and a high defect rate, averaging 2.46%. The methodologies applied include Value Stream Mapping (VSM) to visualize material and information flow, Process Activity Mapping (PAM) to classify activity types, and the Fishbone Diagram to identify root causes of waste. The analysis revealed that the main forms of waste were excessive transportation, waiting time, and product defects in the final stages. Only 47.86% of the activities were value-added, while the rest were either non-value-added or necessary but non-value-added. Improvement strategies focused on optimizing workstations and implementing the 5S method to maintain sustainable efficiency. Post-implementation results show improved process efficiency and a reduction in non-value-added activities. This study demonstrates that Lean Manufacturing can significantly enhance production performance in traditional food industries.